The Role of Exchange Rate and Non-Exchange Rate Related Factors in Polish Firms' Export Performance - Albinowski, Maciej (World Bank, Washington, DC, 2016)
This paper analyzes the export performance of Polish manufacturing firms. It focuses on the extensive and intensive margins of exports, on the decision to enter export markets and the intensity of exports, given participation, examining price and non-price determinants of export performance. The analysis relies on two different but complementary sources of data: a panel survey of Polish firms for 2005-13, and an exporter-level customs data set, for the same period, with detailed information on products and destinations. The findings reveal that firms face high sunk costs for entering export markets, and that once these costs have been paid, they depreciate rapidly over time. Strong positive local spillovers are also identified, which help reduce entry costs. Finally, the paper shows that the impact of real exchange rate fluctuations on firms' export performance is dependent of the degree of integration in international production networks.